SINERGI PENANGGULANGAN PENYEBARAN VIRUS CORONA PADA MASA PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) DARURAT DI KELURAHAN DELOD PEKEN KABUPATEN TABANAN BALI - Emma Ratna Sari Moedy (Jurnal Ilmiah Cakrawarti, 2021)
In early 2020, the world was shocked by an outbreak of a new pneumonia that started in Wuhan, Hubei Province, which then spread rapidly to more than 190 countries and territories. This outbreak was named corona virus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The spread of this disease has had a broad social and economic impact, including in the aspects of diagnosis, treatment, and prevention. The case study in Delod Peken Village, Tabanan, Bali, Indonesia shows a positive synergy between the central government to the local government and the grassroots. This commitment is reflected in the strong trust and acceptance of President Joko Widodo's instructions for the implementation of the Covid-19 emergency on July 3-20 2021. The will to achieve conditions for reducing the number of infections and deaths is the obligation of every individual, apparatus and government. The complexity of implementation is a challenge. There is no medicine available and the spread of transmission is still high in Delod Peken Village. Synergy in this area occurs because of the awareness of the government and the grassroots to take care of each other and the environment. The government program for immunization of 1 million vaccines per day is a temporary solution. While the long-term solution is how to provide health education from an early age by implementing the 5 M (washing hands with running water, avoiding crowds, keeping a distance, wearing masks) and 3T (testing, trecing, treatment).